Degalactosylated Whey Protein Suppresses Inflammatory Responses Induced by Lipopolysaccharide in Mice - Inui, Toshio; Kawamura, Namiko; Nakama, Riho; Inui, Akio; Katsuura, Goro (Frontiers in Nutrition, 2022)
The effects of degalactosylated whey protein on lipopolysaccharide (LPS)-induced inflammatory responses in mice were observed in comparison with intact whey protein. Intraperitoneal administration of both intact and degalactosylated whey proteins for 5 days did not affect body weight and food intake in mice. On day 6, intraperitoneal administration of LPS induced a marked decrease in body weight 4 h later. The LPS-induced decrease in body weight was significantly suppressed by the administration of degalactosylated whey protein, but not intact whey protein. Administration of LPS also significantly increase plasma tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) levels, which were significantly suppressed by the administration of degalactosylated whey protein, but not intact whey protein. Moreover, the application of degalactosylated whey protein to RAW264.7 cells significantly reduced mRNA expression of toll-like receptor 4 (TLR4) and significantly increased mRNA expression of mitogen-activated protein kinase phosphatase-1 (MKP-1). The marked increased expression of TNF-α and IL-1β in response to LPS in RAW264.7 cells was significantly suppressed by the application of degalactosylated whey protein. These results suggest that degalactosylated whey protein suppresses the effects of LPS in part by decreasing in TLR4 and increasing in MKP-1.